In depth: Global alert: Glaciers are melting at unprecedented rate - Mila Ibrahimova (The UNESCO Courier, 2023)
Glaciers appear on almost every continent providing a large part of the fresh water we consume. But this indispensable resource is now threatened. Today we know that the glaciers in UNESCO World Heritage sites are retreating at an accelerated rate because of climate change. According to the latest report by UNESCO, in partnership with IUCN, World heritage glaciers: sentinels of climate change, they lose on average some 58 billion tons of ice every year – and contribute to almost 5 per cent of global sea-level rise.